Potret Budidaya Padi Lebak oleh Petani Lokal di Kecamatan Pemulutan, Ogan Ilir, Sumatera Selatan - Lindiana Lindiana; Benyamin Lakitan; Siti Herlinda; Kartika Kartika; Laily Ilman Widuri; Erna Siaga; Meihana Meihana (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2016)
Lindiana, et al. Rice Cultivation Images by Local Farmers in Pemulutan District, Ogan Ilir, South Sumatra. JLSO 5(2):153-158. Plans and efforts in increasing rice productivity at riparian wetlands can be commenced by introducing relevant technologies; however, the selected technologies should be based on real needs or problems faced by local farmers. As a pre-requisite, if the needs and problems are not comprehensively understood, government intervention to introduce new technology may not be effective since the technology may not be relevant or affordable to local farmers. Objectives of this research are to analyze characteristics of the wetlands, farmer’s adoption capacity, and technological preferences. The research was conducted in five villages at Pemulutan District. Qualitative Grounded Theory and Quantitative Survey were employed through dialogues with 100 local farmers.  Results of the research indicated that any effort to increase riparian wetland productivity should consider the unpredictability of flood occurrences and prolonged drought. These unfavorable conditions have limited local farmers to only grow rice once per year. Local farmers were almost solely depending on rice and cultivation of other crops were rarely observed, except limited vegetables grown on elevated border of paddy fields.